AKUNTABILITAS PEMERINTAH DESA DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (STUDI PADA ALOKASI DANA DESA DI KABUPATEN GAYO LUES) - Sri Karlinayani; Endang Surasetyo Ningsih (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
According to the Institute of Public Administration and Financial and Development Supervisory Agency of Indonesia (2000: 12), accountability is the obligation to account or answer the performance and actions of a person / leader of an organizational unit to the party who has the right or authority to ask for accountability. Accountability is essential to ensure values such as efficiency, effectiveness, reliability and predictability. This research was conducted in eleven villages in Gayo Lues district is the village Kutelintang, Rerebe, Sekuelen, Rema, Akang Siwah, Rerebe, Ampa Kolak, Tetingi, Uning Pune, Padang and Gajah. This research is a descriptive study using qualitative data and collecting data by interview and documentation. The results showed that of the eleven villages sampled, only one village that has not been prepared in the process of holding the village fund. Constraints experienced by village officials for the financial management of the village is the lack of qualified human resources and financial management schools of the village, causing village officials prefer to use the services of third parties in the manufacture and preparation of reports required for the management of village finances.